Health state utility and health-related quality of life measures in patients with advanced ovarian cancer - Ruby M. van Stein; Florine J. Hendriks; Valesca P. Retèl; Cor D. de Kroon; Christianne A.R. Lok; Gabe S. Sonke; Kelly M. de Ligt; Willemien J. van Driel (Gynecologic Oncology Reports, 2023)
Purpose: Measuring health-related quality of life (HRQoL) in ovarian cancer patients is critical to understand the impact of disease and treatment. Preference-based HRQoL measures, called health state utilities, are used specifically in health economic evaluations. Real-world patient-reported data on HRQoL and health state utilities over the long-term course of ovarian cancer are limited. This study aims to determine HRQoL and health state utilities in different health states of ovarian cancer. Methods: This cross-sectional, multicenter study included patients with stage III-IV ovarian cancer in six health states: at diagnosis, during chemotherapy, after cytoreductive surgery (CRS), after chemotherapy, in remission, and at first recurrence. HRQoL was measured using the European Organization for Research and Treatment of Cancer Core Quality of Life Questionnaire C30, and the ovarian cancer-specific module OV28. Health state utilities were assessed using the EuroQol five-dimension five-level (EQ-5D-5L) questionnaire. Descriptive analyses were performed for each health state. Results: Two hundred thirty-two patients participated, resulting in 319 questionnaires. Median age was 66 years. The lowest HRQoL was observed during chemotherapy and shortly after CRS. Physical and role functioning were most affected and the highest symptom prevalence was observed in the fatigue, nausea, pain, dyspnea, gastrointestinal, neuropathy, attitude, and sexuality domains. Patients in remission had the best HRQoL. Mean utility values ranged from 0.709 (±0.253) at diagnosis to 0.804 (±0.185) after chemotherapy. Conclusions: This study provides clinicians with a valuable resource to aid in patient counseling and clinical decision-making. The utilities, in particular, are crucial for researchers conducting economic analyses to inform policy decisions.